2020
DOI: 10.3390/jpm10040294
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics for Diagnosis and Prognosis of Uterine Diseases? A Systematic Review

Abstract: This systematic review analyses the contribution of metabolomics to the identification of diagnostic and prognostic biomarkers for uterine diseases. These diseases are diagnosed invasively, which entails delayed treatment and a worse clinical outcome. New options for diagnosis and prognosis are needed. PubMed, OVID, and Scopus were searched for research papers on metabolomics in physiological fluids and tissues from patients with uterine diseases. The search identified 484 records. Based on inclusion and exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 115 publications
(97 reference statements)
0
25
0
Order By: Relevance
“…Pertubations in critical pathways involving fatty acid metabolism, choline metabolism, tricarboxylic acid cycle and glycolysis have all been described in the pathogenesis of cancer [ 21 , 33 , 34 ]. Metabolomic biomarkers have shown promise for the early detection of several cancers, including those of the breast [ 35 ], colon [ 36 ] and prostate [ 37 ], and may be particularly relevant in endometrial cancer, given its strong association with obesity, insulin resistance and type 2 diabetes mellitus [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pertubations in critical pathways involving fatty acid metabolism, choline metabolism, tricarboxylic acid cycle and glycolysis have all been described in the pathogenesis of cancer [ 21 , 33 , 34 ]. Metabolomic biomarkers have shown promise for the early detection of several cancers, including those of the breast [ 35 ], colon [ 36 ] and prostate [ 37 ], and may be particularly relevant in endometrial cancer, given its strong association with obesity, insulin resistance and type 2 diabetes mellitus [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, metabolomic profiles of cancer patients (blood, urine, tissue samples, and cervicovaginal lavage) were analyzed and differentiated from those of healthy women and those with benign uterine diseases (e.g., precancerous cervical intraepithelial neoplasia [CIN], cervicitis (Yang et al 2017; Abudula et al 2020; Khan et al 2019; Ilhan et al 2019; Tokareva et al 2020; M. zhu Yin et al 2016; Tokarz, Adamski, and Rižner 2020). As a result, algorithms with high diagnostic properties have been reported (Yang et al, 2017; Abudula et al, 2020; M.…”
Section: Metabolomicsmentioning
confidence: 99%
“…Several investigations found different quantities of aa in plasma or serum for CC, though the results were inconsistent. In plasma, Hasim et al found reduced valine, isoleucine, alanine, histidine, glycine, and glutamine, but Ye et al found greater levels of alanine and glycine in serum (Tokarz, Adamski, and Rižner 2020). Although these metabolites are the basic units for tumours, biomass levels in the blood are aberrant in cancer patients (Wishart 2019).…”
Section: )mentioning
confidence: 99%
“…Metabolomics involves the detailed investigation of metabolites and small molecules closely related to the disease. In CINs and CC, it has been used extensively to study cancer metabolism and identify biomarkers indicative of disease, states, and underlying etiology [155].…”
Section: Metabolomicsmentioning
confidence: 99%